Communities of Remembrance Religious Orders and the Cult of Thomas de Cantilupe, Bishop of Hereford (1275-82) - Bass, Ian L. (2018)
In the chronological list of posthumous miracles attributed to St Thomas de Cantilupe, bishop of Hereford (1275-82, canonized 1320), there are eleven explicit references to religious order in Britain. This article explores some of the themes of these miracle stories as recorded in the surviving contemporary account, Oxford, Exeter College MS 158, and examines their potential to inform our understanding of aspects of monastic life. These accounts allow historians to re-date or extend some abbacies of heads of religious houses, observe the performance of visitations and the care for the sick, and highlight how religious houses were vehicles for communal remembrance and could influence lay dedication to particular cult centres. In order to make these accounts accessible to a wide audience for future use, the article includes the monastic miracles in a fully transcribed and translated appendix with relevant historical notes.